La Gestión de inventario y su influencia en la rentabilidad de la empresa ECOPRAL CIA. LTDA Cantón Pallatanga, periodo 2023-2024 - Bravo Hipo, Achik Pakari (2026)
This research work addresses the impact of incorrect inventory management on the profitability and operational efficiency of the company, generating negative financial performance, and aims to evaluate inventory management and its influence on the profitability of ECOPRAL CIA. LTDA, located in the Pallatanga canton, in the period 2023- 2024. A mixed-methods approach was applied, with a non-experimental, documentary, and field design, based on the hypothetical-deductive method and a descriptive-correlational research design. The population consisted of 14 documents and 4 people. The results show that gross profitability reaches 11.95% in 2023 and 17.93% in 2024, while net profitability reaches 4.04% in 2023 and 5.23% in 2024. It was determined that inventory management positively influences the company's profitability by optimizing resources and increasing profit margins. It was concluded that the company had deficiencies in its inventory management, resulting in losses from expiration and deterioration. Despite the increase in gross and net profitability in 2024, there were risks associated with a lack of logistical control and the absence of automation and clear policies, which compromised operational efficiency and financial stability.